2023
DOI: 10.3389/fmicb.2023.1112035
|View full text |Cite
|
Sign up to set email alerts
|

Integrated enzymes activity and transcriptome reveal the effect of exogenous melatonin on the strain degeneration of Cordyceps militaris

Abstract: As a valuable medicinal and edible fungus, Cordyceps militaris has been industrialized with broad development prospects. It contains a lot of bioactive compounds that are beneficial to our health. However, during artificial cultivation, strain degeneration is a challenge that inhibits the industrialization utility of C. militaris. Exogenous melatonin (MT) can scavenge for reactive oxygen species (ROS) in fungus and can alleviate strain degeneration. To establish the significance and molecular mechanisms of MT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Nevertheless, the number of research studies on the fundamental biology of C. militaris remains limited compared to that of other edible basidiomycete fungus. The lack of information in this area has led to a rapid decrease in production strains over time, and finding an appropriate breeding strategy to address this issue has not been adequately resolved (Yin et al 2017;Lou et al 2019;Xin et al 2019;Zu et al 2023). This lack of an effective breeding system presents a major bottleneck hampering the progress of the C. militaris industry.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the number of research studies on the fundamental biology of C. militaris remains limited compared to that of other edible basidiomycete fungus. The lack of information in this area has led to a rapid decrease in production strains over time, and finding an appropriate breeding strategy to address this issue has not been adequately resolved (Yin et al 2017;Lou et al 2019;Xin et al 2019;Zu et al 2023). This lack of an effective breeding system presents a major bottleneck hampering the progress of the C. militaris industry.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are closely related to spontaneous degradation in C. militaris [37]. Exogenous melatonin (MT) is reported to scavenge oxygenfree radicals in fungal cells, and Zu et al [83] found that the degradation characteristics of a degraded strain of C. militaris under MT treatment were significantly lessened. RNA-seq revealed that compared with the control, glutathione s-transferase genes were up-regulated under MT treatment.…”
Section: Militaris Strain Degradation Mechanismsmentioning
confidence: 99%